A novel submerged photocatalytic oscillatory membrane reactor for water polishing. Issue 4 (August 2021) - Gupta, Siddharth; Gomaa, Hassan; Ray, Madhumita B.
Abstract: A submerged photocatalytic oscillatory membrane reactor was tested for micropollutants removal from water as a tertiary treatment method for water polishing. A detailed study of the system performance at various operating conditions of membrane reactor and background water matrices including humic acid (HA) and secondary wastewater effluent (SWE) was conducted. Initially, the system was evaluated using suspended nanosized TiO2 under UV illumination and antipyrine as a model pollutant. Experiments using central composite design (CCD) and response surface analysis (RSM) were used to analyze the effects of the oscillation amplitude and frequency, and airflow rate on the antipyrine removal and the membrane flux. Optimum conditions for the reactor operation were determined using a composite desirability function. These conditions were then applied for the removal of other micropollutants with varying physiochemical properties namely, diclofenac, sulfamethoxazole, and hydrochlorothiazide. Up to 90% micropollutants removal can be achieved in Milli-Q water, although, the performance was noticeably affected in presence of background organics in SWE and HA due to either catalyst blocking and/or competition of organics, as well as catalyst agglomeration. A significant process intensification can be achieved using the proposed photocatalytic oscillatory membrane reactor configuration, which could offer a promising potential as a final polishing step for water recycling. Graphical Abstract: ga1 Highlights: Submerged photocatalytic oscillatory membrane reactor was used for tertiary treatment. Up to 90% micropollutants removal can be achieved in pure water. Oscillation with aeration was effective in reducing fouling and enhancing membrane flux. Removal of micropollutants was significantly affected in presence of humic acid.